The Application of Dry-Air Blast to the Manufacture of Iron-Supplementary Data - JAMES GAYLE (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
(Presented at the Washington meeting, May 3, 1905, and simultaneously sent to the Iron and Steel Institute, for presentation at the meeting of that Society in London, May 11, 1905.) IT is to be regretted that the data respecting the use of dry-air blast, which was presented to the Iron and Steel Institute at its meeting in the United States, in October, 1904, should. have been restricted to the period from August 25th to September 9th inclusive, and from September 17th to 30th inclusive. In order to present the paper at all it was found necessary to limit the record of operations to the period above stated. In the discussion of the paper it would appear from the conclusions of some participating therein, that they have been placed at some disadvantage in considering the economies obtained through the use of dry-air blast, by reason of the data covering such a short period. It is the purpose of this communication to present in detail the record of operations of the Isabella Furnaces from November, 1904, to March, 1905, inclusive, as shown by the furnace-records. The month of October, 1904, is not included, as the furnace using dry-air blast was stopped several times for repairs, and while the record was a very good one considering these interruptions, yet it was not a continuous one. The record for Furnace No. 1 using dry-air blast, and the comparison with Furnace No. 3 using natural air for the month of November, 1904, is set forth in Table I. By a reference to my former paper it will be noted that the month of November is the beginning in this country of the winter period, when the atmosphere decreases rapidly in humidity. The month of October being the transition month in the autumn and April in the spring, and furnaces using natural air approach more closely, from November on, to the conditions obtained by the use of dry-air blast. The data given in